Sexual Selection - Andersson, M. B. (Monographs in Behavior and Ecology Ser., 1994)
Bright colors, enlarged fins, feather plumes, song, horns, antlers, and tusks are often highly sex dimorphic. Why have males in many animals evolved more conspicuous ornaments, signals, and weapons than females? How can such traits evolve although they may reduce male survival? Such questions prompted Darwin's perhaps most scientifically controversial idea - the theory of sexual selection. It still challenges researchers today as they try to understand how competition for mates can favor the variety of sex-dimorphic traits. Reviewing theoretical and empirical work in this very active field, Malte Andersson, a leading contributor himself, provides a major up-to-date synthesis of sexual selection.